Kepatuhan Penggunaan Alat Pelindung Diri (APD) Terhadap Keselamatan Kerja pada Tenaga Kesehatan di Puskesmas Maiwa Kabupaten Enrekang - Ilma, Nur Ilmayanti; Sulaiman, Zulkarnain; Adri, Khaeriyah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2025)
Personal Protective Equipment (PPE) has a very important role for health workers. One of them is at the Maiwa Community Health Center, health workers are still not compliant with the use of PPE. This study aims to determine the level of compliance with the use of PPE among health workers at the Maiwa Health Center and also to find out what factors influence non-compliance in the use of PPE among health workers at the Maiwa Health Center. In this research, 63 health workers were the research targets using a sample collection technique, namely total sampling. The data collection techniques used in this research were interviews, questionnaires and observation methods. As well as data analysis techniques in this research using validity and reliability tests, bivariate and univariate tests, and chi-square tests. The results of this study show that there is a significant relationship between knowledge and compliance of health workers, proven by a significance value of 0.001 (p-<0.05). The influence of comfort and compliance is proven by a significance value of 0.005 (p<0.05), the influence of supervision and compliance is proven by a value of 0.001 (p<0.05).